Chronotope in Jean-Paul Sartre’s Play “No Exit” - Mayilyan, Alvard (Bulletin of Yerevan University B: Philology, 2022)
The article analyzes the transformation of the classical definition of chronotope in Jean-Paul Sartre's play “No Exit”, the new manifestations of the spatiotemporal concept through the characters' memories and description of the afterlife.Bakhtinian definitions and approaches to the chronotope are explored, as well as new manifestations of the chronotope through the characters' memories, imagination, and anticipation. Spatial and temporal representations of the imaginary world are considered as zero chronotope.
Keywords: existentialism; chronotope; spatiotemporal; concept; hell; sin; chronotope of the author; chronotope of the characters